Denotation and connotation meaning in Little Women: a reflection of liberal feminism through verbal and non-verbal signs in a movie - Maulani, Syafna; Hadiati, Chusni; Yulianita, Nadia Gitya (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2024)
This research aims to determine the meaning of denotation and connotation in Little Women (2019) movie. It employed a qualitative approach. Purposive sampling technique was used to select verbal and non-verbal signs containing feminism issues. In analyzing the data, this research applied Barthes’ (1986) semiotics and the theory of liberal feminism (Tong and Botts, 2018). The data taken are four scenes in the movie. Based on the analysis, it reveals that the wo findings. The denotation reflects the original, actual, or objective meaning of the non- and verbal signs that has been universally agreed upon. Meanwhile the connotation implies the meaning which is not real and is influenced by the reader/viewer’s feelings, emotions, and cultural values. The signs’ meanings there represent liberal feminism in four fields: workplace, social, domestic, and education fields. In each setting, the girls in the movie are presented to be intelligent, hard-working, strong and sensitive, emphatic, independent, and persistent. With these traits, an individual could be successful in his/her life. Indeed, at the end Jo, as the main protagonist, could realize her dreams.